Stand density management diagrams for roble (Nothofagus obliqua) in the Biobío Region, Chile - Müller-Using, Burkhard; Rodríguez, Rolando; Gajardo, Pablo (BOSQUE, 2017)
This study developed a stand density management diagrams using an allometric size-density relationship, based only permanent plots from the Biobío region and to provide a regional tool to allow a better quantitative control of the intermediate cut in roble (Nothofagus obliqua). We used 20 fragments of pure roble located at different environments in the region of Biobío. To get mortality initiation line and the maximum stand production initiation line, were used theoretical estimates of relative density of 0.60 and 0.40 respectively in relation to the maximum size-density line. In our study, the slope of size-density relationships and maximum size-density line differs significantly from the value determined by other studies developed for roble in the country. Furthermore, the slope of size-density relationships was more negative in the Biobío region for roble, and is indicative of lower growth rates and lower site productivity. It justifies develop models of stand density management diagrams considering specific ecological zones for the same species; furthermore it is necessary to standardize methodologically these studies.